2017
DOI: 10.1111/mec.14385
|View full text |Cite
|
Sign up to set email alerts
|

Multiple hypotheses explain variation in extra‐pair paternity at different levels in a single bird family

Abstract: Extra-pair paternity (EPP), where offspring are sired by a male other than the social male, varies enormously both within and among species. Trying to explain this variation has proved difficult because the majority of the interspecific variation is phylogenetically based. Ideally, variation in EPP should be investigated in closely related species, but clades with sufficient variation are rare. We present a comprehensive multifactorial test to explain variation in EPP among individuals in 20 populations of nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 72 publications
(89 reference statements)
4
85
1
Order By: Relevance
“…Parallel studies of mating systems and extragroup paternity in other Malurus species have revealed considerable diversity, supporting the idea that evolutionary pathways can be traced through phylogenetically‐based comparative analysis (Brouwer et al, ; Buchanan & Cockburn, ). Other Malurus species have also been the focus of studies on breeding biology (Karubian, ; Leitão, Hall, Venables, & Mulder, ; Varian‐Ramos & Webster, ), song and vocalizations (Dowling & Webster, ; Greig & Pruett‐Jones, ; Yandell, Hochachka, Pruett‐Jones, Webster, & Greig, ), plumage and ornamentation (Karubian, ; Lindsay, Webster, & Schwabl, ), ecology and conservation (Driskell et al, ; Murphy, Legge, Heathcote, & Mulder, ; Skroblin, Lanfear, Cockburn, & Legge, ), and phylogeography (Baldassarre, White, Karubian, & Webster, ; Kearns, Joseph, Edwards, & Double, ; McLean, Toon, Schmidt, Joseph, & Hughes, ).…”
Section: Introductionmentioning
confidence: 67%
“…Parallel studies of mating systems and extragroup paternity in other Malurus species have revealed considerable diversity, supporting the idea that evolutionary pathways can be traced through phylogenetically‐based comparative analysis (Brouwer et al, ; Buchanan & Cockburn, ). Other Malurus species have also been the focus of studies on breeding biology (Karubian, ; Leitão, Hall, Venables, & Mulder, ; Varian‐Ramos & Webster, ), song and vocalizations (Dowling & Webster, ; Greig & Pruett‐Jones, ; Yandell, Hochachka, Pruett‐Jones, Webster, & Greig, ), plumage and ornamentation (Karubian, ; Lindsay, Webster, & Schwabl, ), ecology and conservation (Driskell et al, ; Murphy, Legge, Heathcote, & Mulder, ; Skroblin, Lanfear, Cockburn, & Legge, ), and phylogeography (Baldassarre, White, Karubian, & Webster, ; Kearns, Joseph, Edwards, & Double, ; McLean, Toon, Schmidt, Joseph, & Hughes, ).…”
Section: Introductionmentioning
confidence: 67%
“…Third, the V. moorii territories in our study were on average 2.5 m away from one another, well within typical travel distances for adult fish. Close proximity between breeding territories is expected to facilitate extra‐pair fertilizations, as has been found in birds (Brouwer et al., ; Mayer & Pasinelli, ; Westneat & Sherman, ). Fourth, we also expected that in socially monogamous fishes with biparental care, such as V. moorii , cuckoldry by paired males would be facilitated because fry would not be left unattended in the temporary absence of the male.…”
Section: Discussionmentioning
confidence: 87%
“…Absence of seasonal plumages in M. amabilis is based on Schodde (). % EPY = levels of extra‐pair paternity (proportion of offspring sired by extra‐pair males; Brouwer et al., ; N/A: no data available) are shown for each species, as well as whether there is evidence that seasonal plumages function in female choice and/or male–male competition (this study; Karubian et al., ; Peters et al., ; Fan et al., )…”
Section: Introductionmentioning
confidence: 78%
“…Like most other Malurus , the species breeds cooperatively, forms long‐term social partnerships and displays seasonal plumages, as both breeder and subordinate males moult annually from a dull nonbreeding plumage into a conspicuous breeding plumage (Peters, Kingma & Delhey, ). The timing of moult into breeding plumage by male fairy‐wrens is viewed as a classic female choice‐driven trait: early moult is strongly selected by female choice for extra‐pair (EP) mates who dominate fertilisations (Peters et al., ; Brouwer et al., ; Figure ). However, EP mating is very limited in M. coronatus (<5% of broods) and mostly driven by incest avoidance (Hidalgo Aranzamendi, Hall, Kingma, Sunnucks & Peters, ; Kingma, Hall & Peters, ; Kingma, Hall, Segelbacher & Peters, ), suggesting no role of female EP mate choice in the evolution of male breeding plumage in this species (Figure ).…”
Section: Introductionmentioning
confidence: 99%